Formation and peculiarities of advertising campaign - Yu.O. Golovchuk; L.V. Dibchuk (Економіка, управління та адміністрування)
Advertising is often a reflection of society, constantly follows the latest trends. Marketing experts use it as a tool for emotional reactions. Brands combine powerful messages based on a well-researched idea and effective delivery methods that impact their audience. However, with the ever-changing paradigm of media consumption, control over how the message is delivered has shifted from marketing experts to consumers. The problem of advertising has outgrown creative messages and impressive visuals. It's about finding the best way to deliver a message that will reach the consumer at the right time and place, and it all uses a new range of tools. Advertising is an investment in your business and it is similar to other investments that are designed to improve and expand your business. The investment you will receive depends on the plan and thoughts that precede the commitments and expenses. By developing effective advertising first, you plan to increase the possibility of a positive return on your advertising investment, regardless of the amount of money you spend. Therefore, the strategy of a successful advertising business campaign is an important factor for every company and business. Whether you are watching television, flipping through a magazine, or listening to the radio, which every time offers to buy a product or get a service. Today, not enough attention is paid to the development of an effective advertising campaign. Enterprises are limited in financial resources and do not approach comprehensively to the evaluation of the advertising campaign effectiveness, so this leads to a reduction in the budgets of enterprises. And while there has been a lot of discussion about whether advertising is effective, and whether there are people who buy relevant products, the reality is that many companies spend billions on advertising with the hope that it will increase their profits. Good advertising has the power to encourage people to notice and buy a product, the ways to create an effective advertising campaign have become much more complex. The article defines that advertising is the most important means for promotion of goods of the enterprise on the market. Two main methods of market research are defined as primary and secondary research. The most common methods of marketing promotion is studied, namely: advertising, advertising promotion, promotional gifts, contests, postcards. The analysis of marketing strategies of product promotion of the enterprise is carried out. Creating and implementing an advertising campaign is not an easy task. Thousands of advertising agencies around the world are crowded with people who have spent their lives learning the art of advertising.